Can Training in Employability Skills Help Adolescent Girls and Young Women in South Africa Increase Their Employment Opportunities? - Jean Damascene Mvunabandi; Msizi Mkhize; Ferina Marimuthu; Bomi Cyril Nomlala; Lawrence Gadzikwa (Universitas Proklamasi 45, 2023)
This article investigated how employability skills training can be used to foster adolescent girls' and young women's employment opportunities and to improve their employment pathways in South Africa. This study adopted quantitative and descriptive research approaches via longitudinal data collection. Secondary data was collected from 3584 AGYWs using a questionnaire survey during employability training from July-October 2021. Robustness analysis was performed using descriptive statistics using SPSS version 28.0. The empirical findings proved that employability skills training significantly improved the capabilities of adolescent girls and young women on labour market assessments. Relying on these empirical findings, this study proposes a framework for linking AGYWs and the labour market through an employability skills training capability-based conceptualised model. The results of this study will fill a gap in understanding the twelve dominant employability skills variables identified by this research study which has justified with most relevant literature and theories in particular. This study contributes to the current body of knowledge and further contributes to the career development and employability among adolescent girls and young women required to cope with the labour markets in South Africa. The study recommends schools, Universities and other key role players in skills development among employability skills guidelines for ensuring the readiness of young graduates for employment opportunities in South Africa.